Planning collection routes with multi-compartment vehicles - Oliveira, A.; Ramos, T.; Martins, A. (Operations Research and Big Data: IO2015-XVII Congress of Portuguese Association of Operational Research (APDIO), 2015)
This paper aims to assess the impact of using vehicles with multiple compartments in a recyclable waste collection system. Such systems perform single-material routes to collect three types of recyclable materials (paper, glass and plastic/metal), where vehicles with a single compartment are used. If vehicles with multi-compartments were used, two or even the three materials could be collected simultaneously without mixing them. A heuristic approach is developed to solve the multi-compartment vehicle routing problem and applied to a real recyclable waste collection system operating in Portugal.